Роль некоторых факторов в процессе индукции каллусогенеза in vitro у эфиромасличных растений - Егорова, Н.А.; Ставцева, И.В.; Якимова, О.В.; Каменек, Л.И.; Кривохатко, А.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. The influence of some factors on callus formation for main and perspective for growing in Ukraine species of essential oil plants was investigated. Methods. Cell, tissue and organ culture in vitro, statistics. Results. The conditions for obtaining callus cultures using a wide range of explants, varieties and samples of essential oil plants – lavender (Lavandula angustifolia), sage (Salvia sclarea), coriander (Coriandrum sativum), fennel (Foeniculum vulgare), essential oil rose (Rosa spp.), yarrow (Achillea millefolium, A. filipendulina, A. setacea, A. nobilis), melissa (Melissa officinalis), tarragon (Artemisia dracuncunus), monarda (Monarda fistulosa, M. citriodora, M. didyma, M. x hybrida) have been optimized. The peculiarities of the influence on the callusogenesis of some factors (genotype and donor plant origin, season, hormonal composition of nutrient medium, type of explant and its orientation to the surface of the medium) were revealed. In particular, for fennel variability in the callus formation frequency of plants within ‘Martsishor’ variety (from 0 to 100%) were detected, for lavender it was shown an increased frequency of callusogenesis at 1.5–2.0 times when leaf placed adaxial side on agar compared with abaxial. Conclusions. The important role of some endogenous and exogenous factors in the induction of callus formation in lavender, sage, coriander, fennel, essential oil rose, yarrow, melissa, tarragon, monarda was shown.